TERAPI REGULASI EMOSI UNTUK MENGELOLA STRES IBU DENGAN ANAK PRA-SEKOLAH - Rinaldi, Martaria Rizky; Putra, Dimas Prastia (Universitas Islam Indonesia, 2023)
In everyday life, mothers caring for preschool children often encounter various challenges. These challenges are related to the behavior of the child, health, and parenting, which can lead to stress. Unmanaged stress can cause physical and psychological disorders. Therefore, stress in mothers with preschool children needs to be addressed. This research aims to determine the effectiveness of emotion regulation therapy on stress in mothers with preschool children. The research participants were seven mothers aged 24 to 36 years (mean = 30) with preschool children. Data collection used the PSS-10 scale, and data analysis employed repeated measures ANOVA. The results of the data analysis showed differences in observations before, after the intervention, and follow-up. Thus, the results indicate a decrease in the perceived stress levels of mothers with preschool children. This suggests that emotion regulation therapy is effective in reducing stress in mothers with preschool children. Mental health practitioners such as psychologists can use emotion regulation therapy to assist mothers with preschool children in managing the stress they experience.